2007
DOI: 10.1093/cercor/bhm142
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Temporal Dynamics of Updating Cognitive Control: An Examination of Error Processing

Abstract: In 2 experiments, we used event-related brain potentials (ERPs) to examine the temporal dynamics of neural processes related to adjustments of cognitive control following errors in the counting Stroop task. The ERPs elicited by errors revealed the error-related negativity (ERN) and error positivity consistent with a large body of literature. In addition, errors were associated with a frontal slow wave between 200 and 2000 ms after the response that was consistent with the activity of neural generators in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
4
42
2
Order By: Relevance
“…The results of the present study seem to be at odds with previous studies reporting posterror slowing predicted by the ERN (Debener et al, 2005;Gehring et al, 1993;MarcoPallares et al, 2008;West & Travers, 2008). It is possible that methodological differences across studies can explain part of the empirical differences.…”
Section: Correlation Between Ern Frn P3 and Slowingcontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the present study seem to be at odds with previous studies reporting posterror slowing predicted by the ERN (Debener et al, 2005;Gehring et al, 1993;MarcoPallares et al, 2008;West & Travers, 2008). It is possible that methodological differences across studies can explain part of the empirical differences.…”
Section: Correlation Between Ern Frn P3 and Slowingcontrasting
confidence: 99%
“…On top of that, there are substantial task differences-inducing different errors-among studies. There are meaningful differences between errors in our four-choice color-discrimination task, on the one hand, and the intrusion errors in a Stroop task (West & Travers, 2008) and errors in a flanker task (Gehring et al, 1993;MarcoPallares et al, 2008), on the other hand. One potentially interesting difference is that errors in Stroop and flanker tasks are characterized by response conflict and therefore also trigger conflict adaptation mechanisms.…”
Section: Correlation Between Ern Frn P3 and Slowingmentioning
confidence: 65%
See 1 more Smart Citation
“…We defined engagement as the overt or covert allocation or focusing of attentional resources. Consistent with engagement's determining ERN amplitude, a recent study showed that ERN amplitude was highest in individuals showing a happy mood state and low self-reported boredom at the beginning of the task and showed the largest decrease in a happy mood and the smallest increase in boredom during the task, suggesting in this case a positive relation to intrinsic motivation that is present only at the beginning of performance (West & Travers, 2008). Another motivator of task engagement may be concerns over so MacDonald, 2008;Segerstrom, 2005), which would increase persistence during prolonged task performance.…”
mentioning
confidence: 64%
“…After the reward manipulation, ERN amplitude and left RFA increased, and RTs and error rates decreased. All the measures showed the largest changes from the first to the second 20-min interval of In addition, a less pronounced increase in state boredom during the task was associated with larger ERN amplitudes (West & Travers, 2008; see also Luu et al, 2000). Constraint shows strong negative correlations with trait susceptibility to boredom (especially the internal stimulation aspect; Culp, 2006), suggesting that this last association (between less pronounced increase in state boredom during the task and larger ERN amplitudes) may have reflected subjects who score high on constraint, who showed less of an increase in state boredom and a smaller decline during the task in ERN amplitudes.…”
Section: Discussionmentioning
confidence: 89%